Carlo Passaglia's De Ecclesia Christi A Trinitarian Ecclesiology at the Heart of the 19th Century - Rossi, Valfredo Maria 1979- (2018)
The purpose of this article is to explore an aspect of the Catholic theology of the 19th century which is relatively unknown: namely the Roman School and Carlo Passaglia's position within it. This contribution is focused on presenting the main theological treatise of Carlo Passaglia (1812-87), De Ecclesia Christi (1853-56), an unprecedented work in the context of 19th-century theology, from which a Trinitarian ecclesiology, rooted in the economy of salvation, emerges. The article will be divided into three parts: the first will provide a brief outline of the Roman School, which played a significant role in the theology of the 19th century; the second will offer a biography of Passaglia; finally, the third will focus on the De Ecclesia and will present a basic survey of the whole monograph in order to highlight the most significant aspects of Passaglia's ecclesiology. Moreover, this contribution will seek to emphasize that several aspects of Passaglia's Trinitarian ecclesiology went on to be developed by the Second Vatican Council, particularly in Lumen Gentium.
Keywords: 19th-century theology; Carlo Passaglia; De Ecclesia Christi; Roman School; Trinitarian ecclesiology